Karakterisasi Simplisia dan Uji Aktivitas Antioksidan Ekstrak dan Fraksi Daun Pidada Merah (Sonneratia caseolaris L): Characterization and Evaluation of Antioxidant Activity of Red Pidada Leaves (Sonneratia caseolaris L) - Eka Siswanto Syamsul; Supomo; Siti Jubaidah (KOVALEN: Jurnal Riset Kimia, 2020)
Research on red Pidada leaves (Sonneratia caseolaris L.) which is a mangrove plant with antioxidant potential has been carried out. This study aims to determine the simplicia characterization and activity of red Pidada leaf extracts and fractions as antioxidants. The results of the simplicia characterization were: water-soluble extract content of 11%, ethanol-soluble extract content of 16%, water content of 9%, ash content of 8.17%, and acid insoluble ash content of 0.48%. The antioxidant activity test was carried out using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The antioxidant activity was determined by the IC50 (Inhibition Concentration) value. The results showed that the ethanol extract had an IC50 value of 24.22 ppm (very strong), n-hexane fraction 88.18 ppm (strong), ethyl acetate fraction 15.39 ppm (very strong), and ethanol fraction 38.41 ppm (very strong) Keywords: Sonneratia caseolaris L., antioxidants, DPPH, IC50